Land Subsidence in the Yangtze River Delta, China Explored Using InSAR Technique From 2019 to 2021 - Hongbo Jiang; Guangcai Feng; Yuexin Wang; Zhiqiang Xiong; Hesheng Chen; Ning Li; Zeng Lin (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The combined effects of global warming and human activities have intensified land subsidence (LS), limiting the sustainable development of economy in delta regions. Despite the potential of interferometric synthetic aperture radar (InSAR) for monitoring LS, its application across vast delta regions may be hindered by complex data processing, high computational demands, and the need for standardized results. To overcome these challenges, we adopted the multitemporal InSAR technique, integrating a frame data parallel processing strategy and an overall adjustment correction method, to obtain the temporal deformation sequences of the entire Yangtze River Delta (YRD) region in China from January 2019 to December 2021. We calculated the annual average deformation rate and identified deformation areas, with 73.5% concentrated along the Yangtze River, along the coastline, and within the northern Anhui mining area. A significant correlation was observed between LS and anthropogenic activities, such as economic development and land reclamation activities. Further analysis reveals that the increase in GDP growth rate may contribute to LS. Approximately, 38% of the reclaimed area in the YRD is at risk of LS. Land reclamation activities present a dichotomy, with Hangzhou Bay as the dividing line. This study provides a new perspective and scientific basis for understanding and analyzing LS in deltaic environments, contributing to sustainable development and advancing wide-area InSAR deformation monitoring.